2008
DOI: 10.1038/cdd.2008.51
|View full text |Cite
|
Sign up to set email alerts
|

Role of non-canonical Beclin 1-independent autophagy in cell death induced by resveratrol in human breast cancer cells

Abstract: Resveratrol, a polyphenol found in grapes and other fruit and vegetables, is a powerful chemopreventive and chemotherapeutic molecule potentially of interest for the treatment of breast cancer. The human breast cancer cell line MCF-7, which is devoid of caspase-3 activity, is refractory to apoptotic cell death after incubation with resveratrol. Here we show that resveratrol arrests cell proliferation, triggers death and decreases the number of colonies of cells that are sensitive to caspase-3-dependent apoptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
279
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 388 publications
(298 citation statements)
references
References 39 publications
15
279
0
4
Order By: Relevance
“…Beclin-1-independent pathways of autophagy are being elucidated. 39 We suggest that in nonHodgkin lymphomas not expressing beclin-1 the chemotherapy regimen should include drugs able to induce beclin-1-independent autophagy. Finally, the data here reported show that the immunohistochemical detection of beclin-1 (and of LC3) in nonHodgkin lymphoma has a great prognostic potential.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Beclin-1-independent pathways of autophagy are being elucidated. 39 We suggest that in nonHodgkin lymphomas not expressing beclin-1 the chemotherapy regimen should include drugs able to induce beclin-1-independent autophagy. Finally, the data here reported show that the immunohistochemical detection of beclin-1 (and of LC3) in nonHodgkin lymphoma has a great prognostic potential.…”
Section: Discussionmentioning
confidence: 94%
“…In a few cases, tumours with a low percentage of beclin-1-positive cells presented with a relative high proportion of LC-3-positive cells, which is suggestive of the activation of a beclin-1-independent autophagy pathway. 39 Although the number of cases examined for LC3-positivity was relatively small (36 cases), and despite they were arbitrarily chosen as representative of the whole series, the data obtained indicate (1) that beclin-1 macro-aggregates associate with functional autophagy (as assessed by vacuolar LC3-positivity) in the majority of the cases (71%), and (2) that upregulation of autophagy (assumed as X20% LC3-positive cells) in the tumour context associates with a favourable outcome.…”
Section: Discussionmentioning
confidence: 99%
“…19 Also, downregulation of BECN1 with sh-BECN1 inhibited autophagy in MCF-7 cells. 17,19,[40][41][42] Although it is debatable whether BAF inhibits the fusion of autophagosomes and lysosomes, BAF is still used as an inhibitor to study autophagic flux in many studies. 43 Recently, Shingu et al reported that imatinib, a drug of molecular targeted therapy, induced autophagy in human malignant glioma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Amongst the autophagy genes, beclin-1/ATG6 is a key initiator of autophagy in mammalian cells Cao and Klionsky, 2007), although it may be bypassed under certain conditions (Chu et al, 2007;Scarlatti et al, 2008). Beclin-1 was first identified as a protein that interacts with the anti-apoptotic proteins Bcl-2 and Bcl-xL, but not with Bax/Bak (Liang et al, 1998), and classified recently as a BH3-only protein (Oberstein et al, 2007;Maiuri et al, 2007b).…”
Section: Introductionmentioning
confidence: 99%